Recent Advances on The Enhanced Thermal Conductivity of Graphene Nanoplatelets Composites: A Short Review - Danial, Wan Hazman; Abdul Majid, Zaiton (2021)
Graphene nanoplatelets (GNPs) have attracted significant attention in the field of thermal management materials due to their unique morphology and remarkable thermal conductive properties. In addition, their impressive thermal properties make them interesting nanofillers for producing multifunctional composite materials with a multitude range of applications. This work specifically reviews the recent advances of the application of GNPs as nanofillers for the development of enhanced thermal conductivity of various materials or composites. In this review, the insight on the improved thermal conductivity of the composites bestowed by the GNPs with comprehensive comparison are briefly discussed. This review might unlock windows of opportunities and paves the way towards the production of enhanced materials for thermal applications including electronics, aerospace devices, batteries, and structural reinforcement.